Analisis Kemampuan Berpikir Kritis Siswa Kelas V dalam Menyelesaikan Soal Cerita Matematika untuk Mendukung Profil Pelajar Pancasila - Najah, Putri Safinatun; Yunus, Mahmud; Iva (JENTRE, 2025)
This study was conducted to identify the level of critical thinking skills of fifth-grade students in solving mathematical word problems to support the Pancasila Student Profile at SDN Pejaten Barat 11. A qualitative descriptive method was applied. Data collection techniques included written tests, conversation, and evidence involving students and the fifth-grade homeroom teacher. The results of the study signify that utmost fifth-grade students still demonstrate a low level of critical thinking capability, with the highest achievements in the indicators of interpretation, analysis, and evaluation. Both inter and outer factors impress students' critical thinking skills, including learning motivation, literacy and numeracy abilities, and the learning environment. The critical thinking abilities of fifth-grade students in solving word problems have been shown to support the execution of the Pancasila Student Profile, particularly in the dimensions of critical reasoning and independence.